Introduction - Zalta, Anja; Abbas, Tahir; Azak, Umut (Poligrafi, 2021)
The study of ethnic minorities is of vital concern in the context of nations consisting of different groups, some of which are immigrants whilst others are indigenous to the land. While a considerable degree of effort is made concerning studying the real-world situations of minorities in Western Europe and North America, there are generally limited approaches to exploring the situation in the Middle East. Similarly, although there is important work on the experiences of minorities in Turkey being published, few examine minority groups holistically in terms of elaborating on the current state of affairs as well as situating the analysis into a wider discussion on the nature of ethnic and religious differences in contemporary Turkey. This special issue is an attempt to explore the nature and reality of the lived experiences of ethnic and religious minorities in Turkey from different conceptual and analytical perspectives, ranging from the sociological, historical, and anthropological to the political.